Diversity and ecology of fungi associated with termites of different feeding and nesting group at Pulau Tiga, Sabah - Ng, Jye Kae (2016)
The main objectives were to Isolate and Identify fungi from nest material and gut of three different termite species (Macrotermes gilvus, Dicuspiditermes nemorosus and Microcerotermes dubius) and to screen bioactive compound extracted from the selected isolated fungi. 365 pure isolates strains were successfully isolated from 2835 isolation by using Potato Dextrose Agar (PDA), Malt extract-Yeast extract Agar (MEA) and Carboxymethyl Cellulose (CMC) agar. Of these, 165 (45.21%) pure strains were isolated from Macrotermes gilvus, 136 (37.26%) from Dicuspiditermes sp. and 64 (17.53%) from Microcerotermes dubius. In detail, 29 (7.95%) isolates from Macrotermes gilvus guts, 79 (21.64%) isolates from mounds material and 57 (15.62%) isolates from fungus combs. For Dicuspiditermes sp., 48 (13.15%) isolates from guts and 88 (24.10%) isolates from nest material. For Microcerotermes dubius, 34 (9.32%) isolates from guts and 30 (8.22%) Isolates from nest materials. Fifty eight different species of fungus were Identified (Aspergillus c/avatus, A. flavus, A. nidulans, A. niger, A. ochraceous, A. oryzae, A. penicillioides, Penicillium brevicompactum, P. chrysogenum, P. citrinum, P. citrinum complex, P. glaucum, Penicillium spp., Oidium sp., Helminthosporium sp., Paecilomyces Ii/acinus, Paecilomyces sp., Trichoderma harzianum, Trichoderma sp., Botrydiplodia theobromae, Altenaria sp., Beauveria sp., Chaetomium sp., Cylindrocladium sp., Gliocladium sp., Humicola spp., Pestalotiopsis sp., Phomopsis sp., Scedosporium sp., Trichothecium sp. and Verticillium sp.). Prominent morphological characteristics were highlighted in species description. In this study, 45 Isolates were found to possess cellulolytic ability and the largest yellow halo zone shows are 63mm in diameter. Further, 33 Isolates were found showing strong antimicrobial activity againts Escherichia coli, Staphylococcus aureus, Salmonella enteritidis, A. niger, A. flavus and A. parasiticus. The study showed that the particular fungi isolated from termite gut and nest materials have cellulolytic activity and also some can inhibit the growth of some pathogenic fungi and bacteria.